The Use of RAP Strategy in Improving Reading Comprehension Of EFL Students - Desi Surayatika (Global Expert: Jurnal Bahasa dan Sastra, 2018)
AbstractThe aim of the study was to find out whether there was a significant improvement of students’ reading comprehension achievement after being taught by using RAP strategy or not. The population was all the students of Information System at Indo Global Mandiri University. The sample consisted forty students which was selected by using Purpossive sampling. In collecting the data, a test was used and there was fifty items of multiple choice questions. The data was analyzed by using t-test (Paired Samples t-test). The findings showed that RAP strategy was significant in improving the EFL students’ reading comprehension achievement. It can be seen from the mean of the pre-test and post-test which shows that there was significant difference in students’ reading comprehension after being taught reading by using RAP Strategy. The students who were taught reading by using RAP Strategy had better higher achievement in comprehension after having the treatment. In conclusion, the use of reciprocal teaching strategy could improve the students’ reading comprehension.Keywords : reading comprehension, RAP strategy AbstrakTujuan dari penelitian ini adalah untuk mengetahui apakah ada peningkatan yang signifikan dari pencapaian pemahaman membaca siswa setelah diajarkan dengan menggunakan strategi RAP atau tidak. Populasinya adalah seluruh mahasiswa Sistem Informasi diUniversitas Indo Global Mandiri. Sampel dalam penelitian ini terdiri dari empat puluh siswa yang dipilih dengan menggunakan Purpossive sampling. Tes terdiri dari lima puluh pertanyaan pilihan ganda yang digunakan sebagai teknik untuk mengumpulkan data. Dalam penelitian ini, t-test digunakan sebagai teknik untuk menganalisa data (Paired Samples t-test). Temuan menunjukkan bahwa strategi RAP signifikan dalam meningkatkan pencapaian pemahaman membaca siswa EFL. Hal ini dapat dilihat dari hasil rata-rata pre-test dan post-test yang menunjukkan bahwa ada perbedaan yang signifikan dalam pemahaman membaca siswa setelah diajarkan membaca dengan menggunakan Strategi RAP. Siswa yang diajar membaca dengan menggunakan Strategi RAP memiliki pencapaian pemahaman yang lebih baik. Dapat disimpulkan bahwa penggunaan strategi pengajaran RAP dapat meningkatkan pemahaman membaca siswa.Kata kunci: pemahaman bacaan, strategi RAP